Problematika Peninjauan Kembali Dalam Sistem Peradilan Pidana Pasca Putusan Mahkamah Konstitusi Dan Pasca SEMA RI No. 7 Tahun 2014 (Suatu Analisa Yuridis Dan Asas-Asas Dalam Hukum Peradilan Pidana) - Gumbira, Seno Wibowo (UI Scholars Hub, 2016)
Problems of extraordinary legal remedy on Reconsideration, especially in the criminal justice process in Indonesia following the Ruling of judicial review of the Constitutional Court Number 34 IPPU-XI I 2013 and SEMA Decree No. 7 of 2014 issued by the Supreme Court had the same problem juridical in contradictory with the principles both within the criminal justice system and the principle of the science of law in Indonesia, those principles include the principle of ne bis in idem, the principle of justice which one quick, simple and low cost, the principle of litis finiri oportet, It is on the principle of lex superior derogate legi inferior. It can also be said that the judicial review of the Constitutional Court has the potential to undermine the pillars of legal systems as when stating a legal provision is only base on one law, in which is in fact the legislation is incontracdictory with other laws. The solution that does not cause the problems is that the Supreme Court did not need to issue SEMA Decree No. 7 of 2014 the court simple use the Law of Judicial Power and the Law of the Supreme Court which states Reconsideration should be only one time in addition to the necessary optimizeevidence of proof in the criminal justice process by all Parties.